Study on designer surface plasmon resonators - Gao, Fei (2016)
The thesis presents the functional and structural design of designer surface plasmon resonators, and studies novel physics induced by coupling between multiple resonators. Chapter 1 introduce the basic properties of surface plasmon polaritons which is supported on the interface between dielectrics and metal in optical range, and how to mimic them with artificial plasmonic metamaterials in low frequencies. Chapter 2 introduces a dispersion tuning method on designer surface plasmon resonators. As an example, high-order multipolar modes are enhanced, which are absent in previous studies. Experimental results successfully verify the existence of high-order modes. Chapter 3 studies two horizontally coupled two-dimensional resonators. Our study reveals that, selective excitation of two modes of opposite parity can flip the sign of coupling strength between the pair of resonators. The two modes are degenerate multipolar modes with opposite parity. Near-field experiments verify this sign reversal phenomenon. Chapter 4 studies two vertically stacked two-dimensional resonators. This vertical coupling can be strong enough to induce interference between multipolar modes of successive orders. Spectral minimums associated with asymmetrical line-shapes are observed in near-field transmission spectra. We then construct a vertical chain of these resonators, and find that vertical coupling enables vertical transport of subwavelength surface electromagnetic modes. Chapter 5 implement a two-dimensional electromagnetic topological structure with two-dimensional modified designer surface plasmonic resonators. With the help of structural flexibility of this artificial structure, various time-reversal-invariant defects are implemented to probe the limits of robustness of electromagnetic topological edge states. Experimental results show that although all defect are time-reversal-invariant, some of them can still break the topological protection, which are consistent with simulation results. Chapter 6 extends a two-dimensional cylindrical resonator to a three-dimensional spherical resonator. Incorporating with effective media model, Mie theory is developed to predict the electromagnetic response of the designed spherical structure. Scattering experiments are conducted and verify the above prediction.